THE EFFECT OF HALAL CERTIFICATION AND PRICE PERCEPTION ON PURCHASING DECISIONS (Survey of Ms Glow Skincare Consumers in Subang Regency - Nelly Agustin; Devy W Apriandi; Asep Sugandi (STIESA Press, 2021)
The halal cosmetics industry is rapidly growing due to high market demand. People are beginning to change and recognize the significance of using halal products. Cosmetic lovers prefer Halal-labeled beauty products because they not only beautify the skin, but the raw materials used are guaranteed to be safe. Companies that manufacture beauty products compete to present various types of beauty products, such as facial skincare, powder, lipstick, bodycare, and so on. MS Glow, a local beauty brand that provides complete facial care products for Indonesian women, is one of the brands presents. The purpose of this study was to determine the impact of halal certification and price perception on purchasing decisions (a survey of consumers of MS Glow skincare products in Subang Regency). This study employs the descriptive method in conjunction with an explanatory survey. Primary data were obtained by distributing questionnaires, and secondary data were obtained from a variety of books, journals, internet media, and literature that can be used as references in research. Purposive sampling was used to distribute questionnaires to 100 respondents online. The result of this study show that Halal Certification and Price Perception have a significant effect on purchasing decisions for MS Glow skincare products. For additional research, it is preferable to include the variables studied that influence the purchasing decision variables on MS Glow skincare, such as trust variables, brand image, brand ambassadors, and so on. This study can be used as a reference material for future research to obtain relevant results that improve on the findings of this study.